2007
DOI: 10.1016/j.elspec.2006.11.062
|View full text |Cite
|
Sign up to set email alerts
|

Multielectron spectroscopy: Auger decays of the argon 2p hole

Abstract: All the different Auger decay paths of Argon 2p holes have been characterized using a time of flight spectrometer of the magnetic bottle type. All electrons (the photoelectron and up to three Auger electrons) are detected in coincidence and resolved in energy. Double Auger decay is shown to proceed either through a direct process or by intense cascade paths, implying highly excited autoionizing Ar 2+ states, which are identified as Ar 2+ 3s -2 correlation satellites. TripleAuger decay is also observed and esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
57
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 34 publications
13
57
0
Order By: Relevance
“…One of today's most powerful multielectron coincidence techniques is based on a magnetic bottle for the measurement of electron flight times [5], as recently introduced by Eland et al [6] and implemented at synchrotron radiation sources for inner-shell studies by Penent et al [7]. The magnetic bottle technique makes it possible to obtain detailed information on the photoionized states as well as various decay paths as has been demonstrated by Penent et al [7] for the Xe 4d case and by Lablanquie et al for the Ar 2p case [8]. A major strength of coincidence experiments is the possibility to project specific signals from the multidimensional data sets, where signals from competing processes may overlap with each other and hide features of interest, as we shall demonstrate in this work.…”
Section: Introductionmentioning
confidence: 99%
“…One of today's most powerful multielectron coincidence techniques is based on a magnetic bottle for the measurement of electron flight times [5], as recently introduced by Eland et al [6] and implemented at synchrotron radiation sources for inner-shell studies by Penent et al [7]. The magnetic bottle technique makes it possible to obtain detailed information on the photoionized states as well as various decay paths as has been demonstrated by Penent et al [7] for the Xe 4d case and by Lablanquie et al for the Ar 2p case [8]. A major strength of coincidence experiments is the possibility to project specific signals from the multidimensional data sets, where signals from competing processes may overlap with each other and hide features of interest, as we shall demonstrate in this work.…”
Section: Introductionmentioning
confidence: 99%
“…Electron Detection. The magnetic bottle spectrometer we have employed uses an adaptation of the design by Lablanquie et al 30 to experiments with the bunch period of BESSY II, which is 800 ns. We have therefore shortened the drift tube to 60 cm.…”
Section: Nphys-2009-06-00979amentioning
confidence: 99%
“…In double Auger, by contrast, the two Auger electrons share the available excess energy, dividing it between them with a distribution, which is in principle unknown. Recent coincidence studies of the double Auger effect in atoms [2][3][4][5] have shown that both "direct" and "cascade" pathways exist, giving continuous and discrete electron distributions, respectively. Cascade pathways involve the formation of intermediate doubly ionized states with quantized energies and measurable widths ͑lifetimes͒.…”
Section: Introductionmentioning
confidence: 99%